PENGEMBANGAN KOMPETENSI ASN DI KANTOR BKD MELONGUANE KABUPATEN KEPULAUAN TALAUD - AWALLA, EUNIKE; TULUSAN, FEMMY; LALOMA, ALDEN (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: This study by using qualitative methods. Informant research consists of head of the agency, secretary,and heads of fields. Staff / executives; all amounted to six State Civil Apparatus. Implementation of competencedevelopment of State Civil Apparatus has been applied by local government, although for the development ofcompetence has not become a priority of regional needs based on regional content not only based on fulfilmentof fundamental need of organization, performance management and competence development still limited bylack of budget and managing staff. The state of apparatus / employee in Local Employment Agency RegencyTalaud Islands generally have good work performance. Development of the competence of the State CivilApparatus Local Employment Agency Talaud District personnel agency is programmed through education,training and training. The development of apparatus competence is also done through the workplace.Therefore, this research recommends some things as follows: 1) In order to improve the ability of employees,sending employees to follow the structural training prioritized those who have held positions / those who aremore senior both in terms of rank and work period. So as not to cause social jealousy among employees. Besides,for the requirements to occupy a position really fulfilled. 2) Implementation of merit system can support thedevelopment of employee competency in the office of the Regional Personnel Agency of Talaud IslandsRegency. As well as to overcome the development of spoil system and ensure the bureaucracy is filled byprofessional people then Law 5 of 2014 mandates the application of civil servant management based on merit.Keywords: Competence Development, State Civil Apparatus (ASN)